1993
DOI: 10.1007/bf00198370
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin solution structure changes upon protonation of the N-terminus in dimethyl sulfoxide

Abstract: With the combined use of various two-dimensional (2D) NMR techniques, a complete assignment of the 1H and 13C resonances of oxytocin, Cys-Tyr-Ile-Gln-Asn-Cys-Pro-Leu-Gly-NH2, for two molecular states, protonated and unprotonated at the N-terminal group, was performed in dimethyl sulfoxide. A small but distinct change in the backbone conformation of the six-residue cyclic moiety, associated with the protonation, was first suggested from those NMR parameters relevant to conformation, such as change with temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The polarization-transfer matrix, R, 30 ϫ 30 in size, was determined with a FORTRAN program for the nonlinear leastsquares method by using the Levenberg-Marquardt algorithm. The initial R was estimated linearly from experimental signal intensities with a short mixing time (25 where F j () is the single-quantum (SQ) dipolar lineshape function of spin j under CH couplings. The linewidths for F j () were determined primarily from the experimental SQ lineshapes obtained with a 2D chemical-shift resolved CH dipolar spectrum (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polarization-transfer matrix, R, 30 ϫ 30 in size, was determined with a FORTRAN program for the nonlinear leastsquares method by using the Levenberg-Marquardt algorithm. The initial R was estimated linearly from experimental signal intensities with a short mixing time (25 where F j () is the single-quantum (SQ) dipolar lineshape function of spin j under CH couplings. The linewidths for F j () were determined primarily from the experimental SQ lineshapes obtained with a 2D chemical-shift resolved CH dipolar spectrum (26).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental peak intensities are caused by both direct and relayed polarization transfer mechanisms, but R gives the rates caused by the direct dipolar couplings (25). Thus the determination of R provides the distance information only from direct dipolar couplings.…”
Section: Polarization-transfer Matrix Analysis Of Cross-peak Intensitmentioning
confidence: 99%
“…Previous conformational studies of OXT by nuclear magnetic resonance (NMR) have been readily performed in solvents such as dimethyl sulfoxide (DMSO) [2 -5] and have shown that the assignment of almost all of the 1 H and 13 C resonances of OXT can be obtained in DMSO solvent. [4,6] Furthermore, it has been reported that a conformational difference between DMSO and water greatly affected the amide NH protons. [7] Although NMR spectra of OXT in water have been partially analyzed, there are no reports on the complete 1 H, 13 C, and 15 N resonance assignments because of the difficulty in obtaining NMR spectra sufficient for precise elucidation of the conformation of OXT.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 two b-turn structures were also reported on the basis of the results of NMr spectroscopy experiments involving oxytocin. [5][6][7] A first b-turn structure was proposed in a cyclic cys1-tyr2-Ile3-Gln4-Asn5-cys6 pentapeptide involving the sequence tyr2-Ile3-Gln4-Asn5, and a second b-turn structure was proposed in the c-terminal sequence cys6-Pro7-Leu8-Gly9.…”
Section: Europeanmentioning
confidence: 99%
“…[5][6][7] A first b-turn structure was proposed in a cyclic cys1-tyr2-Ile3-Gln4-Asn5-cys6 pentapeptide involving the sequence tyr2-Ile3-Gln4-Asn5, and a second b-turn structure was proposed in the c-terminal sequence cys6-Pro7-Leu8-Gly9.the structure of oxytocin complexed with a receptor 8-9 and the biological activities of [metal ion---oxytocin] complex [10][11][12][13][14][15][16][17] have been studied by many research groups. …”
mentioning
confidence: 99%